Counseling and discipline practices of selected basic education institutions - Antonio, Gabbi C.; Vinluan, Lorelei R.; Gomez, Marie Grace Avelino; Salubayba, Teodora M. (Quezon City College of Education, University of the Philippines Diliman, 2018)
This study explored the counseling and discipline practices across basic education institutions. Using a qualitative research design, 30 teacher-advisers from private and public schools were involved the study and undergone a series of interviews. Results showed that the issues and concerns assessed are attributed to social and environmental factors.
Thesis
Includes bibliographical references (pages 89-93).
Keywords: Counseling in elementary education; Discipline